Relapse and regression to severe wasting in children under 5 years: A theoretical framework. Issue 2 (3rd November 2020) - Schaefer, Robin; Mayberry, Amy; Briend, André; Manary, Mark; Walker, Polly; Stobaugh, Heather; Hanson, Kerstin; McGrath, Marie; Black, Robert
Abstract: Systematic reviews have highlighted that repeated severe wasting after receiving treatment is likely to be common, but standardised measurement is needed urgently. The Council of Research & Technical Advice for Acute Malnutrition (CORTASAM) released recommendations on standard measurement of relapse (wasting within 6 months after exiting treatment as per recommended discharge criteria), regression (wasting within 6 months after exiting treatment before reaching recommended discharge criteria) and reoccurrence (wasting after 6 months of exit from treatment as per recommended discharge criteria). We provide a theoretical framework of post‐treatment relapse and regression to severe wasting to guide discussions, risk factor analyses, and development and evaluations of interventions. This framework highlights that there are factors that may impact risk of relapse and regression in addition to the impact of contextual factors associated with incidence and reoccurrence of severe wasting more generally. Factors hypothesised to be associated with relapse and regression relate specifically to the nutrition and health status of the child on admission to, during and exit from treatment and treatment interventions, platforms and approaches as well as type of exit from treatment (e.g., before reaching recommended criteria). These factors influence whether children reach full recovery, and poorer nutritional and immunological status at exit from treatment are more proximate determinants of risk of severe wasting after treatment, although post‐treatment interventions may modify risks. The evidence base for many of these factors is weak. Our framework can guide research to improve our understanding of risks of relapse and regression and how to prevent them and inform programmes on what data to collect to evaluate relapse. Implementation research is needed to operationalise results in programmes and reduce post‐treatment severe wasting at scale.